Cortisol response to individualised graded insulin infusions: a reproducible biomarker for CNS compounds inhibiting HPA activation - Chen, Christopher L. H.; Willis, Brian A.; Mooney, Louise; Ong, Guan Koon; Lim, Chay Ngee; Lowe, Stephen L.; Tauscher‐Wisniewski, Sitra; Cutler Jr, Gordon B.; Wiss, Stephen D. (British journal of clinical pharmacology, 2010)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • The insulin tolerance test (ITT) is commonly used to induce cortisol release in response to physiological stress. This methodology can be employed in studies evaluating the hypothalamic‐pituitary‐adrenocortical axis. WHAT THIS STUDY ADDS • An exploration of the threshold for cortisol release in response to blood glucose lowering, indicating that the induction of hypoglycaemia with significant symptoms is not required for a highly reproducible maximal cortisol response. AIM To determine the potential of cortisol secretion, in response to a physiological stressor, as a biomarker for centrally active compounds targeting the hypothalamic‐pituitary‐adrenocortical (HPA) axis. METHODS Cortisol response to hypoglycaemia was measured in 26 healthy males in two stages: firstly to derive an algorithm for individualized, graded insulin infusion rates to achieve defined hypoglycaemic targets over 3 h and secondly to determine the inter‐ and intra‐subject variability of cortisol response to hypoglycaemia over two identical periods by measuring the maximum (tmax), time to maximum (Cmax) response and cortisol area under the response curve (AUC). RESULTS Hypoglycaemia induced a consistent cortisol response starting at approximately 1 h, corresponding to blood glucose concentrations of approximately 3.3 mmol l−1, and peaking approximately 3 h after the start of infusion. The inter‐ and intra‐subject coefficients of variation (CVs) of cortisol response were approximately 19 and 19% (AUC), 15 and 19 % (Cmax) and 10 and 14% (tmax), respectively. The intra‐subject CVs for the ratio of maximum cortisol response to baseline concentration and rate of initial cortisol response between study days were more variable (32.8% and 59.0%, respectively). The blood glucose‐cortisol response model derived from the study was predictive of the individual observed cortisol responses, and estimated a blood glucose EC50 associated with onset of the cortisol response of 3.3 mmol l−1. CONCLUSIONS Gradual hypoglycaemia is an effective, reproducible and well‐tolerated method of stimulating a cortisol response and may therefore be useful in assessing the neuroendocrine response to HPA axis inhibitors, such as corticotropin‐releasing hormone‐1 (CRH‐1) antagonists.